pt (1) \Leftrightarrow 2y^{3}+y=(3-2x)\sqrt{1-x}=2(1-x)\sqrt{1-x}+\sqrt{1-x} \Leftrightarrow y=\sqrt{1-x}(2) TT:\sqrt{2(1-x)+1}-\sqrt{1-x}-(2-x)=0\Leftrightarrow \sqrt{2(1-x)+1}-1-\sqrt{1-x}-(1-x)=0$\Leftrightarrow \sqrt{1-x} (( \sqrt{1-x}\frac{2}{\sqrt{2(1-x)+1}+1}-1)-1)=0 ta có \sqrt{2(1-x)+1}+1\geq2 \Rightarrow \frac{2}{\sqrt{...}+1}\leq 1\Rightarrow \frac{2}{\sqrt{}+1}-1\leq0 \Rightarrow phần gạch chân <0$$\Leftrightarrow x=1 \Rightarrow (x;y)(1;0)$
ĐK: x\leq 1pt (1)
\Leftrightarrow 2y^{3}+y=(3-2x)\sqrt{1-x}=2(1-x)\sqrt{1-x}+\sqrt{1-x} \Leftrightarrow y=\sqrt{1-x}(2) TT:
\sqrt{2(1-x)+1}-\sqrt{1-x}-(2-x)=0\Leftrightarrow \sqrt{2(1-x)+1}-1-\sqrt{1-x}-(1-x)=0$\Leftrightarrow \sqrt{1-x}
\left[ \sqrt{1-x}
(\frac{2}{\sqrt{2(1-x)+1}+1}-1)-1
\right]=0
ta có \sqrt{2(1-x)+1}+1\geq2 \Rightarrow \frac{2}{\sqrt{...}+1}\leq 1$$\Rightarrow \frac{2}{\sqrt{
..}+1}-1\leq0
\Rightarrow $ phần gạch chân $<0\Leftrightarrow x=1 \Rightarrow (x;y)(1;0)$